SEJARAH KAMPUNG KAUMAN SEMARANG (MENGUAK SISI SOSIAL DAN EKONOMI) TAHUN 1992 -2012 (Journal of Indonesian History, 2014)
Kauman is a village in the District of Semarang Central. The village is inhabited not only by the inhabitants of Java races but there are also derived from the Arabic and Chinese descendants. Kau-man society upholds the principle of family relationships are always harmonious society. The prob-lems studied in this research are: 1. How does the history of social development Kauman in Hyder-abad in the year 1992 to 2012? 2. What is the history of economic development Kauman in Sema-rang in 1992 to 2012? In different societies Kauman flow and confidence to get the same treatment in the community. None of them got different treatment (discrimination) in society. In addition to not distinguish between religious beliefs, community Kauman also does not distinguish social sta-tus. Kauman into miniature diversity of Indonesian society, along with all the problems of life and motion. Historically Kauman closely with the stigma of a religious center which is also very thick with the feel of a growing culture in a diverse society, and on the other hand Kauman shows anoth-er face as the lifeblood of economic activity Semarang residents. Kampung Kauman merupakan sebuah kampung yang ada di Kecamatan Semarang Tengah. Kam-pung ini dihuni tidak hanya oleh penduduk ras Jawa tetapi ada juga yang berasal dari keturunan Arab dan Tionghoa. Masyarakat Kampung Kauman menjunjung tinggi asas kekeluargaan dengan membina hubungan bermasyarakat yang selalu harmonis. Permasalahan yang dikaji dalam penelitian ini adalah 1. Bagaimanakah sejarah perkembangan sosial Kampung Kauman di Sema-rang pada tahun 1992 – 2012? 2. Bagaimanakah sejarah perkembangan ekonomi Kampung Kau-man di Semarang pada tahun 1992 – 2012? Di Kampung Kauman masyarakat yang berbeda aliran maupun kepercayaan mendapatkan perlakuan yang sama di dalam masyarakat. Tidak ada satupun yang mendapat perlakuan berbeda (diskriminasi) dalam bermasyarakat. Di samping tidak mem-bedakan kepercayaan atau agama, masyarakat Kampung Kauman juga tidak membedakan status sosial. Kampung Kauman menjadi miniatur kebhinnekaan masyarakat Indonesia, berikut dengan segala gerak hidup dan persoalannya. Secara historis Kampung Kauman erat dengan stigma pusat keagamaan yang juga sangat kental dengan nuansa budaya yang berkembang dari dalam masyara-katnya yang beragam, dan di lain pihak Kampung Kauman menunjukkan wajah yang lainnya se-bagai urat nadi kegiatan perekonomian warga Kota Semarang.